Ghrelin modulates innate immune and ileal responses to lipopolysaccharide administration in weaned pigs - Burdick Sanchez, Nicole C.; Dailey, Jeffery W.; Broadway, Paul R.; Davis, Emily M.; Bowen, Brooke M.; Petry, Amy L.; Ballou, Michael A.; Hales, Kristin E.; Carroll, Jeffery A. (Frontiers in Animal Science, 2025)
Ghrelin is a hormone that is mainly produced in the stomach and is known to stimulate feed intake. Recent evidence suggests that ghrelin may affect immunity. This study evaluated whether repeated administrations of ghrelin prior to and following an inflammatory challenge (lipopolysaccharide, LPS) would alter the innate immune response. Weaned pigs (n = 36; age, 21 days) were housed in individual pens and were fitted with temperature loggers on day −7 and jugular vein catheters for serial blood collection on day −3. Based on body weight (BW), the pigs were separated into two treatments: 1) Ghrelin—administered human ghrelin (5 µg/kg BW, i.v.) every 12 h from −48 to 36 h relative to the administration of LPS at 0 h; and 2) Control—administered a similar volume of saline and LPS. Blood samples were collected at various time points relative to the administration of LPS. At 48 h, the pigs were humanely euthanized, and samples of the jejunum and ileum were collected for histology. Ghrelin pigs gained more weight (p = 0.04) and had greater average daily gain (ADG) (p = 0.02) compared with the Control pigs. There was a treatment × time interaction (p = 0.03) for flank temperature, in which Ghrelin pigs had greater body temperature at 0, 2, 4, and 48 h post-LPS administration. The neutrophil concentrations and the neutrophil:lymphocyte ratio were reduced (p ≤ 0.04) in Ghrelin compared with Control pigs. There was a treatment × time interaction (p = 0.03) for eosinophil concentrations, in which Ghrelin pigs had reduced eosinophils compared with Control pigs at 0 and 36 h post-LPS administration. There was a treatment × time interaction for serum concentrations of tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-γ), granulocyte–macrophage colony-stimulating factor (GM-CSF), and interleukin 4 (IL-4) (p ≤ 0.04), with greater concentrations observed in Ghrelin compared with Control pigs. In the ileum, Ghrelin pigs had greater villus length and reduced villus blunting scores, lacteal dilation scores, and lamina propria eosinophil counts compared with Control pigs (p ≤ 0.04). The data from this study suggest that ghrelin may provide some protection against endotoxin-induced inflammation in the ileum while increasing the basal concentrations of cytokines. Further research is necessary to fully understand the impact of ghrelin on the inflammatory response in weaned pigs.